Pengaruh Cashless Society Dan E-Wallet Terhadap Perilaku Konsumtif Mahasiswa - Rahmi, Restu Aulia; Maresti, Dwila; Zuhra, Syarifah (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
This study aims to analyze the influence of cashless society and e-wallets on the consumptive behavior of students at Mohammad Natsir University Bukittinggi. The research method used a quantitative approach with a survey technique on 70 respondents selected by purposive sampling. Data were analyzed using validity tests, reliability tests, classical assumption tests, and multiple linear regression. The results show that e-wallets have a positive and significant effect on consumptive behavior (β = 1.059; p = 0.000), while cashless society shows a significant negative influence (β = -0.306; p = 0.008). Simultaneously, both variables explain 69.8% of the variation in consumptive behavior (Adj. R² = 0.698). These findings indicate that e-wallet features such as cashback and ease of transaction are the main triggers of consumptive behavior, while a comprehensive understanding of the cashless system can act as a controller. This study recommends the importance of digital financial literacy and more responsible e-wallet design.